Wanderings : Sudanese migrants and exiles in North America - Abusharaf, Rogaia Mustafa (Anthropology of contemporary issues., 2002)
In one of the first books devoted to the experience of Sudanese immigrants and exiles in the United States, Rogaia Mustafa Abusharaf places her community into context, showing its increasing historical and political significance. Abusharaf herself participates in many aspects of life in the migrant community and in the Sudan in ways that a non-Sudanese could not. Attending religious events, social gatherings, and meetings, Abusharaf discovers that a national sense of common Sudanese identity emerges more strongly among immigrants in North America than it does at home. Sudanese immigrants use informal transatlantic networks to ease the immigration process, and act on the local level to help others find housing and employment. They gather for political activism, to share feasts, and to celebrate marriages, always negotiating between tradition and the challenges of their new surroundings.Abusharaf uses a combination of conversations with Sudanese friends, interviews, and life histories to portray several groups among the Sudanese immigrant population: Southern war refugees, including the "Lost Boys of Sudan," spent years in camps in Kenya or Uganda; professionals were expelled from the Gulf because their country's rulers backed Iraq in the Gulf War; Christian Copts suffered from religious persecution in Sudan; and women migrated alone.